Treatment failure of bacterial vaginosis is not associated with higher loads of atopobium vaginae and gardnerella vaginalis - Ferreira, Carolina Sanita Tafner [UNESP] (2017)
Purpose. Cervicovaginal Atopobium vaginae and Gardnerella vaginalis are strongly associated with bacterial vaginosis (BV) and are the main components of vaginal biofilms. The low efficacy of BV treatment with metronidazole may be due to the presence of such biofilms. Thus, the aim of this study was to compare the pretreatment cervicovaginal loads of A. vaginae and G. vaginalis for women who restored normal flora and those who persisted with BV after a full course of oral metronidazole. Methodology. In this cross-sectional study, 309 reproductive-aged women were recruited in a primary health care service in Botucatu, Brazil. Cervicovaginal samples were tested for genital tract infections, microscopic classification of local microbiota and molecular quantification of A. vaginae and G. vaginalis. Results. All the participants with concurrent cervicovaginal infections (n=64) were excluded. A total of 84 out of 245 (34.3%) women had BV at enrolment and 43 (51.2%) of them completed the treatment and returned for follow-up. Evaluation of the vaginal microbiota at follow-up showed that 29 (67.4%) women restored normal vaginal flora, while 14 (32.6%) still had BV. The pretreatment loads of G. vaginalis were lower in women with treatment failure (P=0.001) compared to those who successfully restored normal flora. The loads of A. vaginae did not differ between the groups. Conclusion. Although G. vaginalis produces several virulence factors and its loads correlate positively with those of A. vaginae, higher cervicovaginal quantities of these bacteria are not associated with treatment failure of BV after oral metronidazole.